1991
DOI: 10.1093/brain/114.6.2363
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Patterns Associated With Non-Specific Magnetic Resonance Imaging Abnormalities in Temporal Lobe Epilepsy

Abstract: We investigated the cerebral metabolic patterns associated with non-specific hyperintense T2-weighted image on Magnetic Resonance Imaging (MRI) in Temporal Lobe Epilepsy (TLE). Nineteen patients suffering from TLE with a normal CT scan underwent Positron Emission Tomography (PET) using 18F-fluorodeoxyglucose; 8 had hyperintense T2-weighted image on MRI in the epileptogenic temporal lobe and 11 had a normal MRI. Interictally, PET exhibited focal hypometabolism in all the patients with hyperintense T2-weighted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 0 publications
3
43
1
Order By: Relevance
“…However, abnormal electrical activity, both ictal and interictal, is linked to reorganization of language cortex in TLE (Janszky et al, 2003). Furthermore, metabolic PET scans in TLE patients have demonstrated widespread interictal temporal lobe hypometabolism (Ryvlin et al, 1991), and altered anterior and inferior temporal lobe neurotransmitter function (Merlet et al, 2004). Therefore, the absence of significant comprehension deficits after ATL is likely to reflect a preoperative reorganization of the language system in the presence of left-lateralized TLE rather than an absence of language function in this region in the normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal electrical activity, both ictal and interictal, is linked to reorganization of language cortex in TLE (Janszky et al, 2003). Furthermore, metabolic PET scans in TLE patients have demonstrated widespread interictal temporal lobe hypometabolism (Ryvlin et al, 1991), and altered anterior and inferior temporal lobe neurotransmitter function (Merlet et al, 2004). Therefore, the absence of significant comprehension deficits after ATL is likely to reflect a preoperative reorganization of the language system in the presence of left-lateralized TLE rather than an absence of language function in this region in the normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some imaging studies have also suggested that there may be changes in the thalamus ipsilateral to the affected temporal lobe. Interictal positron emission tomography scans from several institutions have shown hypometabolism in the thalamus ipsilateral to the hypometabolic temporal lobe (40,41). There is also a recent report of thalamic atrophy ipsilateral to the atrophic hippocampus that was documented by volumetric measurements (42).…”
Section: Fig 2 A: Ca1mentioning
confidence: 99%
“…It has been shown that there is interictal hypometabolism in TLE patients as well as in epileptic animals, which does not directly correlate with neuronal loss (Ryvlin et al, 1991;O'Brien et al, 1997;Foldvary et al, 1999;Dube et al, 2001). Thus, the regulation of metabolic pathways is most likely disturbed in the epileptic brain.…”
Section: Introductionmentioning
confidence: 99%